Model Matematika Struktural untuk Pertumbuhan Ekonomi dengan Anggaran Pertahanan Sebagai Variabel Endogen - Johnson Kennedy, Posma Sariguna (Universitas Kristen Indonesia, 2022)
In this paper, “a structural mathematical model is made that explains how the variables of economic growth, defence budget, and investment simultaneously interact with one another. The simultaneous equation developed in this study consists of four structural equations: the relationship between defence spending with economic growth, relations with investment, relations with education, and the endogeneity of military expenditures. This equation, there is indicated a simultaneous system of four endogenous variables. The economic growth equation is used as an identity equation, and the defence budget in which there are traditional threat variables defined as autonomous to see the effect of crossing over on economic growth, investment and education budget.Keywords: Structural Mathematical Model, Simultaneous Equations, Economic growth, Economic Defense, Traditional Threats